(untitled) (SCIENCE TIME JOURNAL, 2026)
This article explores productive and interactive forms of enhancing speaking skills within the framework of Bloom’s Taxonomy. Emphasizing higher-order cognitive processes, the study investigates how learners can develop not only their linguistic knowledge but also their ability to apply, analyze, evaluate, and create meaningful utterances in real communicative contexts. Various pedagogical strategies are discussed, including collaborative tasks, role-plays, debates, problem-solving activities, and project-based learning, which promote critical thinking, creativity, and communicative competence. The importance of scaffolding, timely feedback, and learner autonomy is highlighted as essential for effective oral communication. Aligning speaking activities with Bloom’s hierarchical levels significantly enhances learners’ engagement, cognitive development, and confidence in practical communication situations. This study provides valuable insights for educators aiming to optimize speaking skill development in language learning.